Do electoral coalitions facilitate democratic consolidation in Africa? - Resnick, Danielle (SAGE Publications, 2013)
In a region where democratization has led to a proliferation of opposition parties, pre-electoral coalitions represent an obvious means by which to reduce excessive party fragmentation in Africa. However, this article examines whether such coalitions facilitate democratic consolidation in terms of contributing to incumbent turnovers as well as creating competitive, institutionalized party systems. Election data for all opposition coalitions formed in Africa’s electoral democracies since 2000 reveals that coalitions rarely result in incumbent defeat. In addition, I find that a sizeable share of a country’s total electoral volatility is often due to fluctuations in voting for opposition parties that enter and exit coalitions, indicating the inability of coalition members to build loyal constituencies and become institutionalized over time. I argue that this is because many of these coalitions are primarily office-seeking and consist of parties that are distinguished predominantly by the personality of their leaders rather than a distinct political programme that is relevant to the concerns of African citizens.